Facile one-pot synthesis of glycoluril-based porous organic polymers. (9th March 2015) - Wang, Tao; Zhao, Yan-Chao; Luo, Min; Zhang, Li-Min; Cui, Yi; Zhang, Chang-Shan; Han, Bao-Hang
Abstract: Several polymers are constructed through a facile one-pot approach connecting glycoluril with different aldehydes using p -toluenesulfonic acid as both catalyst and solvent in a sealed tube at high temperature. Fourier transform infrared and solid-state 13C CP/MAS NMR spectroscopy are used to elucidate the final structure of the glycoluril based porous organic polymers. The materials, with Brunauer–Emmet–Teller (BET) specific surface area up to 1010 m 2  g −1, possess a high carbon dioxide uptake (up to 12.2 wt% (273 K) and 8.3 wt% (298 K) at 1.0 bar) while a methane uptake up to 4.2 wt% (273 K) at 1.0 bar. Furthermore, the polymers exhibit a hydrogen uptake capacity up to 1.37 wt% (77 K) at 1.0 bar. Graphical abstract: Highlights: Construction of porous polymers through a facile one-pot approach connecting glycoluril with different aldehydes. All the starting compounds are commercially available. Uptake capacities of the polymers for gases are studied.